KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) - Humawida Muthianisa; Kiki Nia Sania Effendi (Department of Mathematics Education, Universitas Kuningan, 2022)
This study was aimed to determine the mathematical representation ability of students at the level of junior high school class IX. The subjects in this study were students of class IX B in one of the junior high schools in Klari District, Karawang Regency who were randomly selected with a total of 25 students. The method applied in this research is descriptive qualitative. The instrument in this research is by testing the ability of mathematical representation of the material of a two-variable linear equation system as many as 3 description questions. The data analysis technique used in the study consisted of data reduction, data presentation and conclusion drawing. The results of this study indicate that the mathematical representation ability of class IX B students at the school on the material of a two-variable linear equation system is in the low category.